Curvature of galaxy brightness profiles. Issue Volume 15:Issue S359(2020) (March 2019) - Lucatelli, Geferson; Ferrari, Fabricio; Cortesi, Arianna; Chies-Santos, Ana L.; de Oliveira, Fernanda Roman; de Oliveira, Claudia Mendes; Izuti Nakazono, Lilianne M.
Abstract: Galaxy morphologies reflect the shapes of galaxies and their structural components, such as bulges, discs, bars, spiral arms, etc. The detailed knowledge of the morphology of a galaxy provides understanding of the physics behind its evolution, since the time of its formation, including interaction processes and influence of the environment. Thus, the more precisely we can describe a galaxy structure, the more we may understand about its formation and evolution. We present a method that measures curvature, using images, to describe galaxy structure and to infer the morphology of each component of a galaxy. We also include some preliminary results of curvature measurements for galaxies of the Southern Photometric Local Universe Survey (S-PLUS) DR1 data release and for jellyfish galaxies of the Omega Survey. We find that the median of the curvature parameter and the integrated area under the curvature give us clues on the morphology of a galaxy.